Employing nature to combat floods: some experiences from Malaysia - Chan, Ngai Weng; Ibrahim, Ab. Latif; Kung, Hsiang-te; Liu, Pin-Shuo (Penerbit Ustara, 2002)
Natural undisturbed systems possess inherent mechanisms and their own ways and means of maintaining system stability. Forests and floodplains, also commonly known as wetlands, are nature's way of controlling floods. Forests and wetland forests control floods by controlling rainfall at source, a concept only recently adopted by flood control agencies. Layered and densely forested areas intercept a significant amount of rainfall and regulate the flow of rain down branches, trunks and roots before reaching the river. Interception, the amount of rainfall caught in the forest crown, is about 10 - 15% of total rainfall. Least interception occurs when forests are thinned and exposed due to clearing, while maximum interception (often reaching 100 %) occurs with dense virgin forests made up of evergreen trees. During heavy rainstorms, rainwater commences to drift as mists or droplets to earth as "throughfall" which averages about 75 - 85% of rain in humid climates like Malaysia. Runoff from upstream also has to penetrate the forest before reaching the river, hence increasing lead time. Wetland forests along rivers, estuaries and coastal areas also give runoff from precipitation (which eventually gets into rivers) a place to spread out, serving as natural retention basins. Wetland forests act like sponges soaking and absorbing a lot of water down into the ground and then releasing it slowly over time. As much as 2.3 million litres of water is absorbed per hectare, depending on the nature of the soil. Forests hold the water and release it slowly. When forests are cleared or destroyed, all the rainwater gets into rivers at a relatively rapid time, resulting in flash floods. The concentration of water into the main river channel over a much shorter period of time dramatically increases flooding. It is vital for engineers and all scientists to work with natural systems rather than against them. In this respect, the JPS Malaysia has initiated the mandatory Manual for Environmentally Friendly Drainage for all development projects, indicating an all-important change of mindset from conventional engineering approach to a more comprehensive multiÂ¬disciplinary approach that taps on the expertise of all disciplines.